Relationship Between Attitudes And Media Exposure With Premarital Sex Behavior In Adolescents - Ettore Gagliano (CV. AFDIFAL MAJU BERKAH, 2022)
Adolescent problems related to reproductive health, often stem from a lack of information, understanding and awareness to achieve reproductive health. So that researchers want to know the relationship between attitudes and media exposure with premarital sex behavior in adolescents. Variables studied include media exposure and attitude. The method used in this study is cross sectional design analysis. Population and number of samples as much as 100 people. Data collection using chi square which aims to connect between independent variables and dependent variables. The results of the univariate analysis were mostly low knowledge of adolescents about premarital sex (54%), more exposure to the media (62%), negative attitudes (70%). The conclusion of the results of the research conducted, namely all the variables studied have a meaningful relationship with pre-marital sex behavior in adolescents. Media exposure (p.value 0.00) and attitude (0.01).